COVID-19 and Corporate Balance Sheet Vulnerabilities : A Simple Stress-Test Approach - Feyen, Erik (World Bank, Washington, DC, 2020)
This paper conducts a simple stress test to gauge the ability of listed nonfinancial corporates to withstand shocks to earnings and receivables. It targets two basic accounting ratios that capture a firm’s ability to cover its short-term liabilities and interest expenses. The sample consists of almost 17,000 firms in 73 countries and represents US$22.1 trillion in total assets and US$6.05 trillion in total debt. The findings show that, prior to the pandemic, almost 60 percent of the debt was associated with firms that already exhibited vulnerabilities according to at least one ratio. A 30-percent shock to earnings and receivables raises this to 88 percent, of which 29 percentage points is vulnerable in terms of both indicators, a 230-percent increase compared with before to the pandemic. Firms in East Asia and Pacific, the Middle East and North Africa, and South Asia appear to be the most exposed. Some countries with vulnerable corporate sectors also display weaknesses in insolvency frameworks, which may impede restructurings and write-downs and contribute to a surge in socially inefficient liquidations of cash-strapped but otherwise viable firms.